Pelvic elements of the giant bird Gargantuavis from the Upper Cretaceous of Cruzy (southern France), with remarks on pneumatisation. (November 2016) - Buffetaut, Eric; Angst, Delphine
Abstract: A synsacrum fragment and an incomplete ilium of the giant bird Gargantuavis philoinos are described from the upper Campanian/lower Maastrichtian Montplo-Nord locality at Cruzy (Hérault, southern France). The ilium provides new information about the pelvic morphology of Gargantuavis . Both the synsacrum and ilium are extensively pneumatised. This extensive pneumatisation may be a plesiomorphic feature, but may also have had a weight-reduction function in a large flightless bird.